Pertanggung Jawaban Hukum Pelaku Trafficking In Person Berdasarkan Hukum Internasional Di Indonesia - Gabrielle Valentia Putri Sahetapy; Efie Baadila; Josina Augustina Yvonne Wattimena (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Trafficking in persons is the act of recruiting, transporting, harboring, sending, transferring, or receiving a person by means of the threat of force, use of force, kidnapping, confinement, counterfeiting, fraud, abuse of power or a position of vulnerability, debt bondage or providing payments or benefits. , so as to obtain the consent of the person who has control over the other person, whether carried out within the country or between countries, for the purpose of exploitation or causing people to be exploited, which is a form of violation of Human Rights (HAM) which generally involves women and children. as a victim.Purposes of the Research: This study aims to determine the regulation of trafficking in persons in international instruments and legal accountability for perpetrators of trafficking in persons based on international law.Methods of the Research: This research is a normative legal research using a law approach and a case approach. Sources of legal materials are primary legal materials, secondary legal materials and tertiary legal materials.Results of the Research: The results of the study indicate that the regulation regarding the prohibition of trafficking in persons according to international law is regulated in the 2000 Palermo Convention, especially in Protocol II and implemented by Indonesia with Law no. 21 of 2007. From the data obtained, trafficking in persons is still widespread and has increased, among others, pressure from economic factors, low education levels, falsification of victim's identity documents. The practice of trafficking in persons is a violation of universal human rights to live free from all forms of slavery. The standard of protection and fulfillment of the rights of victims of trafficking must prioritize human rights, prevention, protection and assistance to victims. Effective action to prevent and fight the phenomenon of human trafficking as a transnational crime, especially for women and children, requires a transnational cooperation relationship, especially a comprehensive one in the countries of origin, transit and destination countries.